The Saharan debris flow: an insight into the mechanics of long runout submarine debris flows - Gee, M; Masson, D; Watts, A; Allen, P (1999)
New 3.5 kHz profiles and a series of piston cores from the north-west African margin provide evidence that the Saharan debris flow travelled for more than 400 km on a highly fluid, low-friction layer of poorly sorted sediment. Data suggest that the Saharan debris flow is a two-phase event, consisting of a basal, volcaniclastic debris flow phase overlain by a pelagic debris flow phase. Both phases were emplaced on the lower continental rise by a single large debris flow at around 60 ka. The volcaniclastic flow left a thin deposit less than 5 m thick. This contrasts with the much thicker (over 25 m) deposit left by the pelagic debris flow phase. We suggest that pelagic sediment, sourced and mobilized as debris flow from the African continental margin, loaded and destabilized volcaniclastic material in the vicinity of the western Canaries. When subjected to this loading, the volcaniclastic material appears to have formed a highly fluid sandy debris flow, capable of transporting with it the huge volumes of pelagic debris, and contributing to a runout distance extending over 400 km downslope of the Canary Islands on slopes that decrease to as little as 0.05°. It is likely that the pelagic debris formed a thick impermeable slab above the volcanic debris, thus maintaining high pore pressures generated by loading and giving rise to low apparent friction conditions. The distribution of the two debris phases indicates that the volcaniclastic debris flow stopped within a few tens of kilometres after escaping from beneath the pelagic debris flow, probably because of dissipation of excess pore pressure when the seal of pelagic material was removed.